2018
DOI: 10.1111/anae.14445
|View full text |Cite
|
Sign up to set email alerts
|

Impact of change in head and neck position on ultrasound localisation of the cricothyroid membrane: an observational study

Abstract: The ideal position for performing surgical cricothyroidotomy is with full neck extension. Some authors have recommended marking the cricothyroid membrane before general anaesthesia, typically with the patient's head and neck in a neutral position. The primary aim of this observational study was to determine whether skin marks made over the centre of the cricothyroid membrane with the head and neck in the neutral position moved outside the boundaries of the membrane when the neck was subsequently extended. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…There is some evidence that full neck extension may increase the height of the CTM by as much as 30%. 111 Pre-induction landmarking of the CTM (e.g., by ultrasound or palpation) should also occur in a position of full neck extension, as the CTM location may change significantly when re-positioning from a neutral to an extended position. 111 …”
Section: Implementation Of the Planned Strategy When Difficult Tracheal Intubation Is Predictedmentioning
confidence: 99%
“…There is some evidence that full neck extension may increase the height of the CTM by as much as 30%. 111 Pre-induction landmarking of the CTM (e.g., by ultrasound or palpation) should also occur in a position of full neck extension, as the CTM location may change significantly when re-positioning from a neutral to an extended position. 111 …”
Section: Implementation Of the Planned Strategy When Difficult Tracheal Intubation Is Predictedmentioning
confidence: 99%
“…The mean height of the cricothyroid membrane as measured by two radiologists was 7.89 mm and 7.88 mm in male patients and 6.00 mm and 5.92 mm in female patients. The height of the cricothyroid membrane moreover increases (by up to 20%) when the head and the neck are placed in fully extension [23,29,30], confirming the necessity of performing cricothyroidotomy in this position [30]. It is likely that a decrease in cricothyroid membrane static height as well as in its dynamic height (achieved by extension) may be observed due to calcification associated with the ageing process [28].…”
Section: Surface and Surgical Anatomymentioning
confidence: 90%
“…The measurement of the anterior neck has shown that the distance from the skin to the hyoid bone is highly predictive of difficult mask ventilation and intubation. 30 In a patient with a concern for a 'cannot intubate, cannot ventilate' scenario, front of neck airway sonographic identification of the cricothyroid membrane is more accurate than palpation alone [31][32][33][34] and more rapid for emergency airway access. 35 36 Of note, the cricothyroid membrane is highly dependent on neck position; therefore, one must maintain the same position or (following any movement of the neck) rescan to confirm location before attempting an emergency airway.…”
Section: Airway Ultrasoundmentioning
confidence: 99%
“…41 And finally, it can facilitate nasogastric tube placement. [30][31][32][33][34][35][36][37][38][39][40] Multiple studies have shown the benefit of ultrasound imaging in the correct placement of nasogastric tubes. [42][43][44] See figure 1 for an example of airway ultrasound probe placement, anatomy and sonoanatomy.…”
Section: Airway Ultrasoundmentioning
confidence: 99%